From Rail-Oriented to Automobile-Oriented Urban Development and Back. 100 Years of Paradigm Change and Transport Policy in Berlin - Kunst, Friedemann (TeMA - Journal of Land Use, Mobility and Environment, 2016)
Transport and its side effects are major problems in rapidly growing cities. Car traffic dominates these cities and pollutes the environment without being able to sufficiently secure the mobility of the urban population and goods. A paradigm shift in urban and transport policy will be necessary to change this situation. In spite of its different development dynamics, Berlin is an interesting example to discuss development strategies for rapidly growing cities because in the course of more than 100 years, a twofold paradigm shift has occurred in the city both conceptually and practically: Berlin has shifted from a city dominated by rail traffic to an automobile-oriented city, and has then gradually transformed back into a city in which an intertwined system of public and non-motorized individual means of transport secures the mobility of the urban population. The interdependencies on the conceptual level between urban planning and transport policies as well as on a practical level between urban structures and transport systems can be studied using the example of Berlin. Experiences with the implementation of automobile-oriented planning and the special conditions in the first decade after reunification led to protests, reflection, and a revision of the transport policy. A strategically designed process of integrated planning has brought about a trend reversal, and steered the development of transport in the direction of clearly formulated sustainability-oriented objectives. In this process, the reintegration of transport and spatial planning and a reorganization of institutional structures at the administrative level was of particular importance. Compact, rail-oriented settlement structures like in the metropolitan region of Berlin make it easier to dispense with automobiles than sprawled structures. The residual role that qualitatively improved automobiles will take in the cities of the future will have to be determined by research and practice. What is certain is that an attractive public transport system should form the backbone of urban transport services.